2021
DOI: 10.3390/atmos12111441
|View full text |Cite
|
Sign up to set email alerts
|

Size-Segregated Particulate Matter Down to PM0.1 and Carbon Content during the Rainy and Dry Seasons in Sumatra Island, Indonesia

Abstract: Size-segregated particulate matter (PM) including the PM0.1 fraction, particles ≤0.1 µm, was monitored during the rainy and dry seasons at three different cities in Sumatra island, Indonesia in 2018. In order to identify possible emission sources, carbonaceous components in the particles collected by a cascade air sampler that is capable of collecting PM0.1 particles were analyzed by applying a thermal/optical reflectance (IMPROVE-TOR) protocol. The PM0.1 levels in the Jambi and Pekanbaru areas were similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In addition, ambient PM 0.1 in Vietnam and Indonesia is very progressive. In Indonesia, the study by Amin et al (2021a) [18] and Putri et al (2021) [21] suggested that the PM 0.1 mass concentration in the dry season is higher than in the wet season in all monitoring sites. In addition, the mass concentrations by different monitoring sites have attention as follows, urban > suburban > rural.…”
Section: Pm 01 Mass Concentration In Southeast Asia Atmospherementioning
confidence: 85%
See 2 more Smart Citations
“…In addition, ambient PM 0.1 in Vietnam and Indonesia is very progressive. In Indonesia, the study by Amin et al (2021a) [18] and Putri et al (2021) [21] suggested that the PM 0.1 mass concentration in the dry season is higher than in the wet season in all monitoring sites. In addition, the mass concentrations by different monitoring sites have attention as follows, urban > suburban > rural.…”
Section: Pm 01 Mass Concentration In Southeast Asia Atmospherementioning
confidence: 85%
“…The importance of carbonaceous particulate matter (OC and EC) in the Earth's climate system is becoming more broadly recognized due to its ability to induce climate changes by directly disrupting the Earth's radiative balance via the extinction of incoming solar radiation and indirectly by serving as cloud condensation nuclei (CCN). Carbonaceous particulate matter was also demonstrated to significantly influence air quality and human health [18][19][20].…”
Section: Sources and Characteristics Of Pm 01 In Southeast Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure followed one suggested by the Ministry of Environment of Japan. After collecting samples, the filters were kept in the chamber for at least 48 hours before being re-weighted and held at -20°C to preserve their chemical constancy until consequent analysis [27]. A total of 60 PM0.1 samples were collected in this study.…”
Section: Cascade Sampler For Ambient Pm01mentioning
confidence: 99%
“…However, information on the status and characteristics of PM0.1 and emission sources is still ongoing and only limited information is currently available. Only a few studies have appeared concerning the level and sources of airborne NPs between different locations [6,7,8]. This review article gathers current papers on all aspects of atmospheric UFPs in Thailand.…”
Section: Introductionmentioning
confidence: 99%